Anxiety sensitivity and subjective social status in relation to anxiety and depressive symptoms and disorders among Latinos in primary care. (May 2015) - Zvolensky, Michael J.; Bakhshaie, Jafar; Garza, Monica; Valdivieso, Jeanette; Ortiz, Mayra; Bogiaizian, Daniel; Robles, Zuzuky; Vujanovic, Anka
Highlights: Anxiety sensitivity is related to greater anxiety symptoms among Latinos. Subjective social status is related to greater anxiety symptoms among Latinos. Anxiety sensitivity is related to greater depressive symptoms among Latinos. Subjective social status is related to greater depressive symptoms among Latinos. Anxiety sensitivity and subjective social status seem to interplay with each other. Abstract: The present investigation examined the interactive effects of anxiety sensitivity and subjective social status in relation to anxiety and depressive symptoms and psychopathology among 143 Latinos (85.7% female; M age  = 39.0, SD  = 10.9; 97.2% used Spanish as their first language) who attended a community-based primary healthcare clinic. Results indicated that the interaction between anxiety sensitivity and subjective social status was significantly associated with number of mood and anxiety disorders, panic, social anxiety, and depressive symptoms. The form of the significant interactions indicated that individuals reporting co-occurring higher levels of anxiety sensitivity and lower levels of subjective social status evidenced the greatest levels of psychopathology and panic, social anxiety, and depressive symptoms. The present findings suggest that there is merit in focusing further scientific attention on the interplay between anxiety sensitivity and subjective social status in regard to understanding, and thus, better intervening to reduce anxiety/depressive vulnerability among Latinos in primary care.